Reviewed Study on Impact and Importance of Paralinguistics in Communication: The Impact and Importance of Paralinguistics in ESL Teaching Process (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the most immediate sense, English for Speakers of Other Languages (ESOL) is simply a description of one of the conditions under which language learning occurs. A section on teachers, classrooms and tasks discusses research which investigates the relationships between teaching and learning, including the learning of language form and uptake. A section on learners and learning is concerned with studies of the process of language learning, including factors such as age, aptitude, personality and motivation. A section on ESOL literacy is concerned with research into the teaching and learning of the written language. A section on organization of provision looks at issues of policy, intensity of provision, language support and work-place provision. There is a further section on research methods and a short section of assessment procedures. Paralinguistics in an ESOL classroom and its study is getting more important lately, and Instructors should be very vigilant about what type of paralinguistics they use and, how they execute paralinguistic features in their ESL teaching process.